Changes in the characteristics of superficial electromyography potentials recorded from the horizontal extraocular muscles in children with non-alternating nonaccommodative comitant strabismus after electrical stimulation treatment (Ukrainian Journal of Ophthalmology, 2026)
Background: Electrical stimulation of lateral rectus muscles (LRM) is a physiotherapeutic technique used in the management of non-alternating nonaccommodative comitant strabismus (NNCS). Changes in the ocular neuromuscular system after a course of electrical muscle stimulation have never been assessed previously due to the lack of a method for analysis.Purpose: To determine the characteristics of superficial electromyography (sEMG) potentials recorded from the horizontal extraocular muscles in children with NNCS, and 2) to determine the changes in the ocular neuromuscular system with the help of sEMG before and after a course of electric stimulation of the muscles.Materials and Methods: An electromyography recorder (M-TEST-2) was used to examine 60 children (120 eyes) with NNCS in accordance with the methodology that we have reported previously. The Amplipuls-5 apparatus was used for electrical stimulation of LRMs in 8 children with non-alternating nonaccommodative comitant esotropia (NNCES). To this end, we followed the therapeutic regimen proposed by Yurov and Cherikchi.Results: In NNCES, frequency of sEMG potentials recorded from the medial rectus muscle (MRM) was significantly higher both in the esotropic eye and in the non-affected fellow eye compared to normal pediatric eyes (109.29 ± 15.89 Hz vs 58.67±15.97 Hz, р=0.0001 and 53±3.49 Hz vs 58.67±15.97 Hz, р=0.0001, respectively). In addition, in non-alternating nonaccommodative comitant exotropia (NNCEX) , there was a significant difference in frequency of sEMG potentials recorded from the LRM, between the esotropic eye, but not the non-affected fellow eye, and normal pediatric eyes (102.52±14.45 Hz vs 60±18.6 Hz, р=0.0001, and 53.16±10.03 Hz vs 60±18.6 Hz, р=0.0001, respectively). In children with NNCS, we found an improvement in the imbalance between the characteristics of sEMG potentials recorded from the horizontal rectus muscles after a course of electrical stimulation. An electrical-stimulation efficiency criterion was devised based on Кν, the ratio of the frequencies of the sEMG potentials recorded from the antagonist rectus muscles.Conclusion: In NNCES and NNCEX, frequencies of sEMG potentials recorded from the LRM differed between the esotropic eye and normal pediatric eyes, and those from the MRM differed between the exotropic eye and normal pediatric eyes, respectively. In children with NNCES, electrical muscle stimulation treatment resulted in an improvement in the imbalance between the characteristics of sEMG potentials recorded from the LRM and MRM.
Keywords: non-alternating comitant strabismus; electrical stimulation of the extraocular muscles; superficial electromyography potentials